2020
DOI: 10.1177/1523422320945237
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Leadership: The Impact of a Servant Leader on the Resilience of their Followers

Abstract: The Problem Businesses and their leaders regularly face disruptive change, uncertain economic futures and the pressure of improving employee well-being. To not only withstand these crises but to rebound and even grow stronger, organizations must develop resilient leaders and a resilient workforce. Human resource development (HRD) professionals are responsible for resilience development within an organization and need to understand whether the development of servant leaders also increases leader and workforce r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 44 publications
1
55
0
1
Order By: Relevance
“…It is very difficult for employees to obtain resources by themselves during the crisis. If there is no Model of goal-directed energy and psychology feasible way to replenish resources or energy, the loss of personal resources will definitely erode employees' resilience (Kuntz et al, 2017;Eliot, 2020). Therefore, providing necessary resources to promote employees' resilience is very important for both organizations and employees to overcome the adversities raised by crisis events.…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult for employees to obtain resources by themselves during the crisis. If there is no Model of goal-directed energy and psychology feasible way to replenish resources or energy, the loss of personal resources will definitely erode employees' resilience (Kuntz et al, 2017;Eliot, 2020). Therefore, providing necessary resources to promote employees' resilience is very important for both organizations and employees to overcome the adversities raised by crisis events.…”
Section: Introductionmentioning
confidence: 99%
“…Issues of resilience and engagement at work (including satisfaction and happiness) about servant leadership are addressed by Youssef and Luthans (2007) and Eliot (2020), among others. They emphasize the importance of psychological capital (PsyCap) considered as confidence (self-efficacy) translating into making and putting in the necessary effort to succeed at challenging tasks; optimism about current and future effectiveness; persistence in pursuing goals; and resilience when adversity and problems arise (Luthans, Youssef, and Avolio, 2007;Luthans et al, 2007).…”
Section: Intergenerational Differences As a Challenge Of Leaders In The Process Of Building Commitment Of Employees In A Public Organizatmentioning
confidence: 99%
“…A leader's understanding of these areas and having psychological capital determine a leader's effectiveness. The focus of servant leadership on meeting the needs of their followers, particularly the psychological needs, along with the studies linking servant leadership and increased PsyCap and humble leadership with increased follower resilience, indicate servant leadership can positively impact follower resilience (Eliot, 2020).…”
Section: Intergenerational Differences As a Challenge Of Leaders In The Process Of Building Commitment Of Employees In A Public Organizatmentioning
confidence: 99%
“…The literature search for this study revealed that since 2010 the term leadership yielded thousands of research results from HRD, yet servant leadership resulted in only a handful of titles. HRD research has focused on how servant leadership: can be developed (Coetzer et al, 2017;Phipps, 2010), predicts mentoring (Sims et al, 2021), and result in follower outcomes of resilience (Eliot, 2020) and engagement (De Clercq et al, 2014). In addition, there was an intersectional critique of servant leadership (Liu, 2019) and a proposition that diversity intelligence was an antecedent to servant leadership (Sims, 2018).…”
Section: Significance Of the Study To Human Resource Development (Hrd)mentioning
confidence: 99%